Use of ß-alanine as an ergogenic aid - Derave, W. (Nutritional Coaching Strategy to Modulate Training Efficiency, 2013)
Despite the large variety of so-called ergogenic supplements used by the sporting community, only few of them are effectively supported by scientific proof. One of the recent evidence-based supplements that entered the market is ß-alanine. ß-Alanine is the rate-limiting precursor for the synthesis of the dipeptide carnosine (ß-alanyl-L-histidine) in human muscle. The chronic daily ingestion of ß-alanine can markedly elevate muscle carnosine content, which results in improved exercise capacity, especially in sports that include high-intensity exercise episodes. The use of ß-alanine is exponentially growing in recent years. This chapter aims to (1) discuss the scientific basis and physiological background of ß-alanine and its synthesis product carnosine, and (2) translate these scientific findings to practical applications in sports.